2013
DOI: 10.1186/1746-6148-9-158
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and thrombolytic effects of the recombinant tissue-type plasminogen activator in horses

Abstract: BackgroundTo test the efficacy of the recombinant tissue-type plasminogen activator (rt-PA) alteplase in horses, the thrombolytic effect was tested in in vitro generated equine thrombi. The extent of lysis was determined by measuring the decrease in thrombi weight over a period of 4 hours. In vivo pharmacokinetics of alteplase were determined in 6 healthy horses. A single dose (1 mg/kg) was applied via intravenous infusion over a period of 30 minutes Coagulation-related variables, blood count and clinical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Although the induction of antibodies to urokinase has not been reported, doses greater than 250,000 IU can induce tachycardia and shaking/chillness. 32 A recent in vitro thrombolysis study reported a dose-dependent decrease in thrombus weight induced by t-PA. 48 Addition of more than 3 μg/mL t-PA at the site of an in vitro generated thrombus did not result in a significant increase of thrombolytic activity and thus might be taken as a breakpoint and maximal plasma concentration to be achieved. Based on these findings, it is advocated to administer 1 mg/kg t-PA for optimal lysis of thrombi when infusing systemically.…”
Section: Discussionmentioning
confidence: 97%
“…Although the induction of antibodies to urokinase has not been reported, doses greater than 250,000 IU can induce tachycardia and shaking/chillness. 32 A recent in vitro thrombolysis study reported a dose-dependent decrease in thrombus weight induced by t-PA. 48 Addition of more than 3 μg/mL t-PA at the site of an in vitro generated thrombus did not result in a significant increase of thrombolytic activity and thus might be taken as a breakpoint and maximal plasma concentration to be achieved. Based on these findings, it is advocated to administer 1 mg/kg t-PA for optimal lysis of thrombi when infusing systemically.…”
Section: Discussionmentioning
confidence: 97%
“…Recombinant tissue plasminogen activator has recently been evaluated in vivo and in vitro for its thrombolytic effects in healthy horses. While initial results appear promising more studies are needed to evaluate the safety and effectiveness (Baumer et al, 2013).…”
Section: Complications Of Intra Venous Catheterization In Horsesmentioning
confidence: 99%
“…Baumer et al reported in their in vitro thrombolysis study a dose dependent decrease in thrombus weight induced by rt-PA. Based on these findings, it is recommended to administer no more than 1 mg/kg rt-PA for optimal lysis of thrombi when infusing systemically. 15–17…”
Section: Discussionmentioning
confidence: 99%